HANA SHOP'S STRATEGY IN INCREASING SALES TURNOVER IN WAKATOBI REGENCY ACCORDING TO ISLAMIC ECONOMICS - Asri Anjani; Sitti Rahma Gurudin; La Ode Aslan (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2026)
PURPOSE - This condition has prompted researchers to analyze the characteristics and issues faced by Kedai Hana business owners. Does the marketing strategy concept implemented align with the concept of marketing in Islam (Sharia Marketing).METHODOLOGY - This type of research is qualitative, which is descriptive in nature and tends to use narrative. The data collection techniques used in this study are observation, interviews, and documentation.FINDING - The results showed that Hana Shop's strategy in Wakatobi Regency is quite good, as evidenced by the large number of customers who come every day during the shop's opening hours. Sales turnover at Kedai Hana in Wakatobi Regency has increased significantly, as evidenced by the increase in the number of servings sold from only 15-25 servings per day to 80-90 servings. This increase is also reflected in the shop's revenue, which now reaches around IDR 80,000,000 per month.